Fee for home delivery and monitoring of antiretroviral therapy for HIV infection compared with standard clinic-based services in South Africa: a randomised controlled trial. Issue 12 (December 2022) - Barnabas, Ruanne V; Szpiro, Adam A; Ntinga, Xolani; Mugambi, Melissa Latigo; van Rooyen, Heidi; Bruce, Andrew; Joseph, Philip; Ngubane, Thulani; Krows, Meighan L; Schaafsma, Torin T; Zhao, Theodore; Tanser, Frank; et al.
Summary: Background: Home delivery and monitoring of antiretroviral therapy (ART) is convenient, overcomes logistical barriers, and could increase individual ART adherence and viral suppression. With client payment and sufficient health benefits, this strategy could be scalable. The aim of the Deliver Health Study was to test the acceptability and efficacy of a user fee for home ART monitoring and delivery. Methods: We conducted a randomised trial, the Deliver Health Study, of a fee for home delivery of ART compared with free clinic ART delivery in South Africa. People with HIV who were 18 years or older and clinically stable (including CD4 count >100 cells per μL and WHO HIV stage 1–3) were randomly assigned to: (1) fee for home delivery and monitoring of ART, including community ART initiation if needed; or (2) clinic-based ART (standard of care). The one-time fee for home delivery (ZAR 30, 60, and 90; equivalent to US2, 4, 6) was tiered on the basis of participant income. The primary outcomes were recorded fee payment and acceptability assessed via questionnaire. The key virological secondary outcome was viral suppression with the difference between study groups assessed through robust Poisson regression including participants with viral load measured at exit (modified intention-to-treat analysis). This trial is registered on ClinicalTrials.gov (NCT04027153 ) and is complete, with analyses ongoing. Findings: From Oct 7, 2019, to Jan 30, 2020, 162 participants were enrolled; 82 were randomly assigned to the fee for home delivery group and 80 to the clinic-based group, with similar characteristics at baseline. Overall, 87 (54%) participants were men, 101 (62%) were on ART, and 98 (60%) were unemployed. In the home delivery group, 40 (49%), 33 (40%), and nine (11%) participants qualified for the ZAR 30, 60, and 90 fee, respectively. Median follow-up was 47 weeks (IQR 43–50) with 96% retention. 80 (98%) participants paid the user fee, with high acceptability and willingness to pay. In the modified intention-to-treat analysis of 155 (96%) participants who completed follow-up, fee for home delivery and monitoring statistically significantly increased viral suppression from 74% to 88% overall (RR 1·21, 95% CI 1·02–1·42); and from 64% to 84% among men (1·31, 1·01–1·71). Interpretation: Among South African adults with HIV, a fee for home delivery and monitoring of ART significantly increased viral suppression compared with clinic-based ART. Clients' paying a fee for home delivery and monitoring of ART was highly acceptable in the context of low income and high unemployment, and improved health outcomes as a result. Home ART delivery and monitoring, potentially with a user fee to offset costs, should be evaluated as a differentiated service delivery strategy to increase access to care. Funding: National Institutes of Mental Health.